Adequate Vitamin D Intake but Low Serum Levels in Pediatric Asthma Patients: A Pilot Study, Alberta Children’s Hospital - Sarah Howe McKenna; Tanis R. Fenton; Mary Noseworthy; Mark Anselmo (Canadian Respiratory Journal)
Background. We assessed vitamin D intakes and serum 25(OH) vitamin D levels in pediatric asthma patients on moderate-to-high dose inhaled steroids and compared them to published findings of healthy children in our city. Methods. Parents and/or patients were interviewed to estimate the children’s vitamin D intakes from foods and supplements (using an adapted validated food frequency questionnaire) and asthma duration and management. Vitamin D status: serum 25-hyroxy vitamin D (25(OH)D) was obtained from the medical records. Results. Vitamin D intakes from food and supplements of the asthma patients (n=20, 742 ± 185 IU/day) were significantly higher compared to healthy Canadian children (n=1442, 229 ± 121 IU/day). Despite higher vitamin D intakes, the children had nonsignificantly lower serum 25(OH) vitamin D levels compared to the comparison group. Serum 25(OH)D levels increased by 3.6 nmol/L with each 100 IU of vitamin D intake (95% Confidence interval = 2.0–4.0, R2 = 0.931, and p=0.001). Conclusion. Since adequate vitamin D status in asthma patients is necessary to support bone mineral accretion, it is important to achieve adequate vitamin D status by checking serum 25(OH)D status and supplement accordingly.